Two new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from China - Ye, Bao-Hua; Yin, Zhan; Li, Xin-Jiang (Zootaxa, 2016)
Two new species of the genus Haplotropis Saussure, 1888 from China are described in this paper. The new species Haplotropis xiai sp. nov. is similar to Haplotropis brunneriana Saussure, 1888, but differs from latter by frontal ridge of male widened at median ocellus; tegmina narrower, cover 2/5 tympanum; cercus of male apical half part gently tapering; lower margin of epiphallus with high projection in the middle; anterior margin of pronotum in female with distinct acute angular in middle; length of subgenital plate shorter than width in female. The Haplotropis zhuoluensis sp. nov. is similar to Haplotropis xiai sp. nov., but differs from latter by anterior margin of pronotum reaching hind margin of eyes; length of temina is 1.6 times in male and 1.3 times in female of width; length of interspace shorter than narrowest in mesosternum of male; ancorae of epiphallus oblique inward distinctly, lower margin with high projection in the middle; length of subgenital plate longer than width in female. Type specimens are deposited in the College of Life Sciences, Hebei University, Baoding, China.